A phase II study to evaluate LY2603618 in combination with gemcitabine in pancreatic cancer patients. Issue 1 (December 2017) - Laquente, Berta; Lopez-Martin, Jose; Richards, Donald; Illerhaus, Gerald; Chang, David; Kim, George; Stella, Philip; Richel, Dirk; Szcylik, Cezary; Cascinu, Stefano; Frassineti, G.; Ciuleanu, Tudor; et al.
Abstract Background The aim of this study was to determine whether checkpoint kinase 1 inihibitor (CHK1), LY2603618, and gemcitabine prolong overall survival (OS) compared to gemcitabine alone in patients with unresectable pancreatic cancer. Methods Patients with Stage II-IV locally advanced or metastatic pancreatic cancer were randomized (2:1) to either 230 mg of LY2603618/1000 mg/m2 gemcitabine combined or 1000 mg/m2 gemcitabine alone. OS was assessed using both a Bayesian augment control model and traditional frequentist analysis for inference. Progression-free survival (PFS), overall response rate (ORR), duration of response, pharmacokinetics (PK), and safety (Common Terminology Criteria for Adverse Events [AEs] v 3.0) were also evaluated. Results Ninety-nine patients (n  = 65, LY2603618/gemcitabine;n  = 34, gemcitabine) were randomized (intent-to-treat population). The median OS (months) was 7.8 (range, 0.3–18.9) with LY2603618/gemcitabine and 8.3 (range, 0.8-19.1+) with gemcitabine. Similarly, in a Bayesian analysis, the study was not positive since the posterior probability that LY2603618/gemcitabine was superior to gemcitabine in improving OS was 0.3, which did not exceed the prespecified threshold of 0.8. No significant improvements in PFS, ORR, or duration of response were observed. Drug-related treatment-emergent AEs in both arms included nausea, thrombocytopenia, fatigue, and neutropenia. The severity of AEs with LY2603618/gemcitabine was comparable to gemcitabine. The LY2603618 exposure targets (AUC(0-∞) ≥21, 000 ng∙hr/mL and Cmax ≥2000 ng/mL) predicted for maximum pharmacodynamic response were achieved after 230 mg of LY2603618. Conclusions LY2603618/gemcitabine was not superior to gemcitabine for the treatment of patients with pancreatic cancer. Trial Registration NCT00839332 . Clinicaltrials.gov. Date of registration: 6 February 2009